Physico-Thermal Characteristics of Coconut Coir–Latex Composites for Thermal Insulation in Fishing Vessels - Polaris Nasution; T Ersti Yulika Sari; Budhi Santoso (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Maintaining low storage temperatures on fishing vessels is strongly influenced by the insulation performance and durability of fish-hold lining materials, especially under humid and splash-exposed marine conditions. This study investigates latex–coconut coir composites as a lightweight, locally available, and bio-based candidate for insulation applications in small fishing vessels. Composite specimens were fabricated using a controlled formulation series from neat latex (100/0) to 50/50 latex–coir, with intermediate ratios of 90/10, 80/20, 70/30, and 60/40. The work emphasizes manufacturability, mass-related properties, and moisture behavior relevant to shipboard service. Water absorption was evaluated after 24 h immersion following the general procedure of JIS A 5908, while specific gravity and density were determined using an Archimedes-based method (ASTM D 792) at 23°C. The results show that increasing coir content reduces the dry specimen mass, supporting lightweight panel development, but significantly affects moisture uptake. Neat latex exhibits minimal water absorption (0.846%), whereas coir-containing composites show higher absorption with a non-linear trend, peaking at the 80/20 formulation (17.345%) and decreasing at 50/50 (10.410%). In contrast, specific gravity ( 0.498–0.500) and density ( 497–499 kg/m³) remain nearly constant across formulations, indicating that moisture performance is governed primarily by microstructure (porosity and latex–fiber interfacial sealing) rather than bulk density. These findings highlight the feasibility of latex–coir composites for marine insulation, while underscoring the need for processing optimization and/or surface sealing to improve moisture resistance.